Education for active citizenship - Luigi Guerra (Social Work & Society, 2007)
Trying to give a definition of Citizenship Education is a challenging operation: it is characterized by a variety of meanings flowing from Civic Education (related to knowledge and practice about the system of laws, rules, conventions referring to a particular civil community) to Socio-political education (related to the awareness of being part of the system of cultural elements, values, traditions historically produced by the community itself). It would be not be correct identifying Citizenship Education only with elements of Civic Education, as it would restrict its range to formal level of rules and laws, rights and duties. Otherwise, limiting its understanding only on elements of Sociopolitical Education, would offer the risk of investing in cultural similarities, common roots, values homogeneity, that are strong in giving hold on identity, membership, participation, but so exposed to acts of fanaticism, exclusion of diversity, hostility towards minorities. Therefore, it is necessary to assume that Citizenship Education has to be established on problematic integration of the two presented perspectives, thus founding knowledge and practice about the rules of civil society on the system of values and cultural aspects that every single micro-community (and every single individual) recognizes to be source of the rules: a complex system of various elements made of homogeneity and inhomogeneity, similarities and differences in constant modification an dynamic intercommunication.